2020
DOI: 10.1016/j.laa.2019.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of the anti-regular graph in the spectral analysis of threshold graphs

Abstract: The purpose of this paper is to highlight the role played by the anti-regular graph within the class of threshold graphs. Using the fact that every threshold graph contains a maximal antiregular graph, we show that some known results, and new ones, on the spectral properties of threshold graphs can be deduced from (i) the known results on the eigenvalues of anti-regular graphs, (ii) the subgraph structure of threshold graphs, and (iii) eigenvalue interlacing. In particular, we prove that no threshold graph con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Theorem 2.3 states that that every tree of order n is isomorphic to a subgraph of the connected antiregular graph A n . Aguilar et al [2] showed that a similar property of the connected antiregular graphs holds also for the class of threshold graphs.…”
Section: (Vii)mentioning
confidence: 88%
See 3 more Smart Citations
“…Theorem 2.3 states that that every tree of order n is isomorphic to a subgraph of the connected antiregular graph A n . Aguilar et al [2] showed that a similar property of the connected antiregular graphs holds also for the class of threshold graphs.…”
Section: (Vii)mentioning
confidence: 88%
“…In [2], the authors reported some partial results towards Conjecture 5.1 -more precisely, they prove that this conjecture is true for all threshold graphs of order n except for n − 2 critical cases, and these cases are considered in a recent preprint [60]. Thus, combining the results obtained in [2,60], we can say that Conjecture 5.1 holds. Theorem 5.12.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Since last decade investigation on the spectral properties of adjacency eigenvalues gained lot of attention. We found lot of papers in this direction [1,2,4,6,10,11,12,13,17]. Bapat [4] proved that the number of negative, zero, and positive eigenvalues of a threshold graph can be find out directly from its binary representation.…”
Section: Introductionmentioning
confidence: 99%